2006
DOI: 10.1021/bi0518141
|View full text |Cite
|
Sign up to set email alerts
|

Mini-αB-Crystallin:  A Functional Element of αB-Crystallin with Chaperone-like Activity

Abstract: Alpha-crystallin is a member of the family of small heat-shock proteins (sHSP) and is composed of two subunits, alphaA-crystallin and alphaB-crystallin, which exhibit molecular chaperone-like properties. In a previous study, we found that residues 70-88 in alphaA-crystallin can function like a molecular chaperone by preventing the aggregation and precipitation of denaturing substrate proteins [Sharma, K. K., et al. (2000) J. Biol. Chem. 275, 3767-3771]. In this study, we show that the complementary sequence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
110
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 47 publications
7
110
0
1
Order By: Relevance
“…Various studies have suggested that target protein binding is mediated by the N-terminal domain [95][96][97][98] or the ACD [99][100][101]. Indeed, with regards to the latter, we [18] and others [17,20,102] have shown that isolated ACDs exhibit chaperone function.…”
Section: The Chaperone Mechanism Of Shspsmentioning
confidence: 74%
“…Various studies have suggested that target protein binding is mediated by the N-terminal domain [95][96][97][98] or the ACD [99][100][101]. Indeed, with regards to the latter, we [18] and others [17,20,102] have shown that isolated ACDs exhibit chaperone function.…”
Section: The Chaperone Mechanism Of Shspsmentioning
confidence: 74%
“…We identified 19-to 20-mer sequences with chaperone function from aA-crystallin and aB-crystallin. 12,13 The individual amino acid, the location, and the chain length of the amino acid sequence are important determinants of the function of a specific peptide. For example, while a 19-mer peptide consisting of a 70 to 88 sequence of aA-crystallin is antiapoptotic, sequences 66 to 80 of a 15-mer peptide cause aggregation and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…11 Potential sequences of a-crystallins that exhibit chaperone activity have been identified. 12,13 We previously identified a 19-mer sequence corresponding to beta3 and beta4 regions of aA-crystallin domain, which has similar chaperone activity in vitro to that of aA-crystallin. 12 Further studies have revealed that the 19-mer peptide sequence of aA-crystallin inhibits fibril formation of Ab-amyloid peptides and suppresses the toxic action of Ab-peptide in rat pheochromocytoma (PC12) cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be concluded that the isolated peptides from αA-crystallin and αB-crystallin inhibit fibril formation by Aβ(1-40) by competing for this binding site with monomeric forms of Aβ(1-40) during its aggregation [102,140]. Significantly, this same peptide region appears to mediate the chaperone activity of αB-crystallin against a range of other disease-related, fibril-forming target proteins, including α-synuclein and β2-microglobulin [138,140]. At present, the development of therapeutics for Alzheimer's disease is largely focused on identifying inhibitors of fibril formation by Aβ peptides with some molecules that exhibit high inhibitory activity having progressed to stage III clinical trials [143][144][145].…”
Section: The Region(s) Of α-Crystallin Responsible For Target Proteinmentioning
confidence: 99%